2022-RA-129-ESGO Ultrasound staging of endometrial cancer. (20th October 2022) - Elagwany, Ahmed
Abstract : Introduction/Background: Endometrial cancer is common in old age and can be divided in to type 1 related to estrogen exposure and type 2 not related to estrogen exposure . Staging can be done by MRI along with staging . Ultrasound can be used recently due to advanced technologies in ultrasound. Methodology: Staging of endometrial cancer in a simplified manner is as follows, stage 1 affection of the endometrium with stage 1a as superficial myometrial affection (less than 50% myometrial affection) and 1b as deep myometrial affection (more than 50% affection), stage 2 with cervical affection, stage 3 with pelvic Peritoneum, adenxal, pelvic and paraaortic nodal affection, ascites, positive wash and stage 4 with bladder and rectal affection, inguinal nodes, abdominal metastasis including peritoneal ones. Results: Firstly, We assess the tumor location, size (three diameters), sonomorphology .Secondly, assessment of the Extent of tumor infiltration into the myometrium along with tumor serosa distance especially at the fundus . Thirdly, Cervical stromal involvement is assessed . the extent of tumor stromal invasion whether (≤ 2/3 or > 2/3) or measurement of tumor-free stroma . The last is done by measuring the distance between the tumor and the pericervical fascia which is the paracervix at he level of the cervix and the paracolpos at the level of the vagina .Fourthly, the assessment of the uterine serosa, adenxa and nodal affection . Finally, The spread into the urinary bladder and/or rectum, inguinal nodes and liver, spleen and kidney along with Omentum or abdominal peritoneal lesions (stage 4) can be determined . Conclusion: We present our checklist for ultrasound scanning in cancer cervix.